Combined transcatheter treatment of severe mitral regurgitation and secundum atrial septal defect in an inoperable patient: a case report. Issue 12 (4th December 2021) - Barbieri, Fabian; Landmesser, Ulf; Kasner, Mario; Reinthaler, Markus
Abstract: Background: Chronic mitral regurgitation (MR) is one of the most common valvular heart diseases and is associated with poor outcomes. Although other structural diseases are regularly seen in such patients, concomitant atrial septal defects (ASDs) remain a rarity in the elderly. Case summary: We report a case of an 82-year-old woman with progressive right-sided heart failure (HF) due to MR and an ASD of secundum type, despite optimal medical therapy. Combined transcatheter mitral valve repair (MVR) by utilizing a separate transseptal puncture and ASD closure was performed resulting in amelioration of symptoms. Discussion: Procedural planning for simultaneous transcatheter therapies of coupled structural heart disease entities remains complex. Our case illustrates feasibility of percutaneous edge-to-edge MVR and consecutive closure of a large secundum ASD. Different options of accessing the left atrium should be discussed on an individual basis, while additional ASD closure may be beneficial in terms of right ventricular function and symptoms of right HF.